A Combined “Vasculoplastic” Approach to the Vasculopathic Patient Undergoing Limb Salvage: Understanding the Role of Endovascular Revascularization for Lower Extremity Free Tissue Transfer - Li, Karen R.; Rohrich, Rachel N.; Lava, Christian X.; Gupta, Nisha J.; Hidalgo, Cecelia M.; Episalla, Nicole C.; Akbari, Cameron M.; Evans, Karen K. (Journal of Reconstructive Microsurgery, 2024)
Multidisciplinary care with vascular surgery and plastic surgery is essential for lower extremity free flap (LEFF) success in the chronic wound population with diabetes and peripheral vascular disease. There is a lack of understanding on performing targeted direct endovascular reperfusion on a vessel that will be used as the flap recipient. Our study compares outcomes of patients who received targeted revascularization (TR) to the recipient vessel for LEFF anastomosis versus nontargeted revascularization (NR) of arterial recipients prior to LEFF.LEFF patients who underwent preoperative endovascular revascularization (ER) from July 2011 to January 2023 were reviewed. Location of ER, demographics, perioperative details, and outcomes were collected. TR was performed on the same vessel as the flap recipient and NR was located on a different vessel than the flap recipient.A total of 55 LEFF patients were identified. Overall, 50.91% (n = 28) received TR and 49.1% (n = 27) received NR. Average age was 60.3 ± 10.9 years and average Charlson Comorbidity Index was 5.3 ± 1.9. On preoperative angiogram, the TR group had significantly lower rates of ER above the knee (3.6 vs. 33.3%, p < 0.001). Immediate flap success rate was 98.2%, with no differences between groups (p = 1.000). No significant differences were found in rates of any postoperative flap complications (p = 0.898), takeback (p = 0.352), partial flap necrosis (p = 0.648), or dehiscence (p = 0.729). Both TR and NR groups had similar rates of a postoperative angiogram (42.9 vs. 48.2%, p = 0.694) and reintervention (35.7 vs. 40.7% p = 0.701). Amputation rates were similar between TR and NR (17.9 vs. 14.8%, p = 1.000).Close follow-up with vascular and plastic surgery is required for patients who undergo ER prior to LEFF, as nearly half of our cohort required additional endovascular procedures. Overall, we observed no significant differences in complication rates for the TR and NR groups, informing revascularization strategies for free tissue transfer in a highly comorbid chronic wound population.
Keywords: lower extremity reconstruction; free tissue transfer; endovascular revascularization; critical limb ischemia; vasculoplastic approach